A Case Study of Irrigation Effect on Agricultural Productivity in Pandharpur Tehsil (International Journal of Food and Nutritional Sciences, 2022)
This paper seeks to examine the response of agrarian productivity to irrigation and its impact on growth of agrarian productivity in the Solapur quarter with special references of sample named townlets of case study. In malignancy of the technological developments in furnishing bettered crop kinds and better operation practices in Solapur quarter, husbandry has been considered a adventure as the agrarian productivity is explosively told by the vagrancies of the thunderstorm. thus, irrigation is an important for the agrarian productivity in Solapur quarter. Use of diseases, HVY seeds, use of technology, robotization is nearly grounded on the vacuity of irrigation and its impact of the agrarian productivity in a region. Comparing village differences of agrarian productivity, a profile of agrarian productivity is examined with a focus on effect of irrigation on agrarian productivity in study area. As a result, two really discerned scripts of the changes of agrarian productivity have been observed. The mainobjects of the present exploration paper are to analyses the significance of agrarian productivity and examine the impact of irrigation agrarian productivity in study area. The Kendall’s ranking measure system is used for dimension of agrarian productivity to the collected information of sample townlets in study area. It has been observed that the spatial pattern of irrigation and agrarian productivity extensively unstable from village in the study area.